(untitled) (CIPEEX, 2025)
The Cerrado is one of the most biodiverse biomes in the world, but it is strongly shaped by fire, which influences vegetation structure and animal communities. Insects play a central role in ecosystem functioning, acting as pollinators, decomposers, herbivores, and as a food source for many species, particularly grassland birds. Despite their importance, insect responses to different fire regimes remain poorly understood. This study, conducted in Chapada dos Veadeiros National Park (Brazil), will evaluate the effects of fire frequency and intensity on insect abundance, biomass, and composition, as well as their relationship with grassland bird communities. Insects will be sampled using sweep-net transects during both dry and rainy seasons, identified at the order level, counted, and weighed. Statistical analyses, including ANOVA, Kruskal–Wallis, NMDS, and regression models, will be applied to compare insect communities across areas subjected to different fire regimes (annual, biennial, triennial, and unburned) and to assess correlations with bird abundance. It is expected that fire alters insect availability, directly influencing food resources and the reproductive success of grassland birds. The findings will provide valuable insights for adaptive fire management strategies, strengthening conservation practices in the Cerrado